Which Energy-Growth Hypothesis is Valid in OECD Countries? Evidence from Panel Granger Causality - Pala, Aynur (International Journal of Energy Economics and Policy, 2016)
This paper aims to determine which energy consumption-economic growth hypothesis is valid in OECD countries. For this purpose, we used panel cointegration, panel Granger causality and panel vector error correction model for the period of 1995-2013. Panel cointegration test outcomes support the long-term equilibrium link among economic growth, energy consumption, labor force and capital formation. The consequences obtained from panel vector error correction model suggests that there is evidence of bi-directional causality between energy consumption and economic growth in the short-term. However, a long-run causality is not found between energy consumption and economic growth. This implies indicated that the OECD countries’ economies are founded on energy and the feedback hypothesis is valid in OECD countries. Policy makers in OECD countries consider the feedback effect by employing arrangements to cut energy consumption. Keywords: Energy consumption, economic growth, cointegration, causality, OECD countries JEL Classifications: C23; Q43